Research on compression behavior of coral aggregate reinforced concrete columns under large eccentric compression loading. (1st May 2018) - Da, Bo; Yu, Hongfa; Ma, Haiyan; Wu, Zhangyu
Abstract: The large eccentric compression behavior of 9 coral aggregate reinforced concrete columns (CARCC) and 2 ordinary Portland reinforced concrete columns (OPRCC) was tested. The concrete type, concrete strength grade and reinforcement type were selected as parameters. The crack development, deformation and bearing capacity were investigated. The relationships of load–displacement and load–axial compressive (tensile) strain were established. The applicable calculation model for the ultimate bearing capacity ( N u ) of CARCC under large eccentric compression was suggested. The results showed that the compression behavior of CARCC were similar to OPRCC. Under the same mix proportion, the lateral stiffness and ductility of CARCC of C25 were both worse than OPRCC of C35. Under the same load, the load shared by reinforcements in CARCC was more than that shared by reinforcements in OPRCC. The application of organic new coated steels, 3% calcium nitrate inhibitor and concrete strength grade over C60 in the CARCC was suggested to effectively inhibit reinforcement corrosion and extend the effective service life of the structure. A comprehensive consideration on the effects of reinforcement corrosion and slip of the coated steel on N u of CARCC was performed. Consequently, a calculation model for the N u of CARCC under large eccentric compression was proposed. Highlights: Effects of different factors on the compression behavior of CARCC were tested and determined. Failure mechanism and ultimate bearing capacity of CARCC were investigated. New technique of reinforcement anti-corrosion in marine engineering was proposed. Possible applications of CARCC in marine engineering structures were suggested.